MEMBERIKAN PEMAHAMAN TENTANG KETERTIBAN LINGKUNGAN PADA PKL SUNDAY MARKET MANAHAN SURAKARTA - Dian Esti Nurati (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
The arrangement and management of Street Sellers (thereafter called PKL) in Surakarta City referring to Surakarta City Local Government’s Regulation Number 3 of 2008 about the Arrangement and Management of Street Sellers in Surakarta City is conducted, among others, by arranging and managing Street Sellers in Sunday Market Manahan Surakarta conducting activity every Sunday morning. Surakarta City government has devised to close street sellers of Sunday Market Manahan Surakarta in 2016. Solo Mayor, F.X. Hadi Rudyatmo devised to sterilize Manahan Stadion area from Sunday Market sellers’ activity. Pasar Tumpah (spilled market) generated in Sunday Market Manahan location will be relocated to other location. The policy is still processed currently by Surakarta City Government. City government wants to recover the original function of Manahan Stadium for sport activity purpose. So far, the existence of sellers utilizing road or sidewalk in Manahan Stadium area disrupts the people’s to do exercise. In addition, the pile of rubbish resulting from Sunday Market activity is so high. The cleaning service officers of Cleanliness and Gardening Service (DKP) working are often overloaded when cleaning the rubbish pile resulting from Sunday Market. This one-day trading activity takes three days to clean its rubbish. Through Youth and Sport Service (Dispora), in this case Surakarta City’s Local Technical Service Unit of Sport Infrastructure, Solo City Government released Joint Decree approved by Dispora, Trade Service of Surakarta City and Street Seller Association of Sunday Market Area. In the presence of Community Service activity, several benefits can be achieved: Successfully giving understanding to the street sellers of Sunday Market about Environment Orderliness in trading location, in Manahan Stadium area of Surakarta; successfully encouraging the street sellers to encourage the City Government’s program to recover the original function of Manahan Stadium for sport activity purpose for Solo City people, so that they no longer use road and sidewalk in Manahan Stadium area; successfully giving an understanding on the importance of maintaining the cleanliness of Sunday Market area, by obliging the sellers to clean rubbish after their activity has been completed; and successfully giving understanding on the importance of maintaining plant as the park (garden) in Sunday Market area. Keywords: Management and Arrangement, Understanding on Environment Orderliness, Street Sellers of Sunday Market